2007
DOI: 10.1002/jor.20372
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of scaffold and growth factor‐mediated repair of critically sized bone defects

Abstract: An 8-mm rat segmental defect model was used to evaluate quantitatively the ability of longitudinally oriented poly(L-lactide-co-D,L-lactide) scaffolds with or without growth factors to promote bone healing. BMP-2 and TGF-b3, combined with RGD-alginate hydrogel, were co-delivered to femoral defects within the polymer scaffolds at a dose previously shown to synergistically induce ectopic mineralization. A novel modular composite implant design was used to achieve reproducible stable fixation, provide a window fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
206
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 236 publications
(213 citation statements)
references
References 29 publications
7
206
0
Order By: Relevance
“…Samples were covered in saline gauze after dissection until testing. The torque-rotation curve was used to calculate the maximum torque and torsional stiffness (slope of the linear region) for each sample [31].…”
Section: Biomechanical Testingmentioning
confidence: 99%
“…Samples were covered in saline gauze after dissection until testing. The torque-rotation curve was used to calculate the maximum torque and torsional stiffness (slope of the linear region) for each sample [31].…”
Section: Biomechanical Testingmentioning
confidence: 99%
“…The recent development of well-controlled external fixation systems for the rat allows exploration of how mechanical stimulation in terms of the IFM can temporally influence the healing process [7,24,29,30,32,37].…”
Section: Introductionmentioning
confidence: 99%
“…Bone formation, through bone volume quantification, has generally been used to evaluate the in vivo scaffold performances [21][22][23]. Bone formation can be observed inside the scaffold as early as 1 week after implantation [24].…”
Section: Introductionmentioning
confidence: 99%
“…To support this approach, we have previously shown that controlled mechanical loadings on rat knee increase the bone volume fraction in polymeric scaffold implanted in the distal femur [19]. Indeed, bone adapts to mechanical stimulation by optimizing its mechanical properties [15], a process regulated by the interplay between bone formation and bone resorption [20].Bone formation, through bone volume quantification, has generally been used to evaluate the in vivo scaffold performances [21][22][23]. Bone formation can be observed inside the scaffold as early as 1 week after implantation [24].…”
mentioning
confidence: 99%